Exploring Students’ Learning Style and Proficiency at a University in Indonesia: A Quantitative Classroom Research - Achmad Yudi Wahyudin; Asti Wahyuni (TEKNOSASTIK, 2022)
This study is designed to confirm whether there is a relationship between students’ learning styles and their English Proficiency at one of private universities in Indonesia. Using quantitative classroom research, 40 students were involved to fill out a questionnaire to explore their learning styles. Then, the students were also required to follow an Institutional English Proficiency Test (EPT) to measure their English ability. The result of the questionnaire is analyzed and presented in terms of visual, auditory, and kinesthetic categories of learning style, while the mean score of students’ English proficiency is presented in terms of low, medium, and high proficiency. The correlational analysis is then calculated to reveal to what extent learning style has a relation to English proficiency. This study bears a pedagogical implication for English teachers and practitioners while some limitations were also highlighted.